Odpowiedzi

Najlepsza Odpowiedź!
2010-03-17T21:09:41+01:00
A) (y-3)-3(x+1) dla x=4, y=2
(y-3)-3(x+1) = y-3-3x-3=y-6-3x
2-6-3*4=-4-12=-16

b) 3(2b+1)-4(a-2) dla a=7, b=1
3(2b+1)-4(a-2) = 6b+3-4a+8 = 6b+11-4a
6*1+11-4*7=6+11-28= -11

c) 9(x-7y)-(5y-2x)+20y dla x=0,5 y=0,3
9(x-7y)-(5y-2x)+20y = 9x-63y-5y+2x+20y = -52x+15y
-52*0,5+0,3*15= - 26+4,5= -21,5

d) (5x+7y)-8(y+1)+3(x-y) dla x=½ y=¼
(5x+7y)-8(y+1)+3(x-y) = 5x+7y-8y-8+3x-3y=8x-4y-8
8*½-4*¼-8=4-1-8=-3-8=-11
2010-03-17T21:18:51+01:00
A) (2-3)-3(4+1)= 1-12-3= -14
b) 3(2+1)-4(7-2)= 6+3-28+8=-11
c) 9(0,5-2,1)-(2,5-1)+6= 4,5-18,9-2,5+1+6=9,9
d) (2,5+1,75)-8(0,25+1)+3(0,5-0,25)=4,25-2-8+1,5-0,75= -4,75
  • Użytkownik Zadane
2010-03-17T21:20:00+01:00
A)(y-3)-3(x+1)=y-2-3x+1=-3x+y-2=-3*4+2*(-2)=-12+-4=-16
b) 3(2b+1)-4(a-2)=6b+3-4a+8=-4a+6b+11=-4*7+6*1+11=-28+6+11=-11
c) 9(x-7y)-5y-2x)+20y=9x-63y-5y-2x+20y=7x-48y=7*0.5-48*0.3=3.5-14.4=-10.9
d) (5x+7y)-8(y+1)+3(x-y)=5x+7y-8y-8+3x-3y=8x+4y-8=8*1\2+4*1\4-8=4+1-8=5-8=-3
Nie wiem czy dobrze:))